Family Problems in Dealing with children Amidst Cultural Shifts: A Field Study in Baghdad - Firas Yousef Qanbar, Assistant Professor Dr. (lark, 2026)
The family is considered the foundamental nucleus the in building society, as it represents the primary framework through which children acquire their values, attitudes, and behaviors However, the family today faces increasing challenges as a result of the rapid cultural. transformations taking place in the world under globalization, media openness, and the development of communication technologies. these transformations have not been limited to changing patterns of thought and behavior but have also extended of affect the nature of relationships within the family particulary between parents strive to presserve authentic social values and traditions, children are exposed to diverse cultural influences that may create a gab in ways of thinking and communication, leading to the emergence of family problems related to upbringing, behaveior regulation and dialogue management Hence, the importance of studying these problems lies in understanding their social and cultural dimensions and exploral mechanisms to address them in a way that a chives a balance between authenticity and modernity, while preserving family cohesion and its educational function.
Keywords: dealing with children; cultural shifts; family problems